2021
DOI: 10.1101/2021.09.02.21262965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing identifies multiple loci for critical illness caused by COVID-19

Abstract: Critical illness in COVID-19 is caused by inflammatory lung injury, mediated by the host immune system. We and others have shown that host genetic variation influences the development of illness requiring critical care or hospitalisation following SARS-Co-V2 infection. The GenOMICC (Genetics of Mortality in Critical Care) study is designed to compare genetic variants in critically-ill cases with population controls in order to find underlying disease mechanisms. Here, we use whole genome sequencing and statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…4C). We note that our proteogenomic screen prioritised SFTPD as a candidate gene for severe COVID-19 in line with other studies 30,32 , leaving the possibility of potential interactions between candidate mediators.…”
Section: Elf5 Is Expressed In Epithelial Cells Of the Respiratory Systemsupporting
confidence: 74%
See 1 more Smart Citation
“…4C). We note that our proteogenomic screen prioritised SFTPD as a candidate gene for severe COVID-19 in line with other studies 30,32 , leaving the possibility of potential interactions between candidate mediators.…”
Section: Elf5 Is Expressed In Epithelial Cells Of the Respiratory Systemsupporting
confidence: 74%
“…The lead cis-pQTL for ELF5, rs766826 (MAF=35.9%), is in strong linkage disequilibrium (LD; r 2 =0.81) with a recently identified variant rs61882275 associated with severe COVID-19 in an independent study using whole genome sequencing 32 . The causal gene remained unidentified, but the two closest candidate genes are ELF5 and CAT , whose encoded protein products are both captured by our proteomic data.…”
Section: Resultsmentioning
confidence: 98%
“…A recent study [39] compared levels of MUC5AC, MUC1 and MUC1-CT between critical ill COVID-19 patients and healthy controls, finding a significantly higher level of those proteins in the patients' mucus. It is also worth noting that another recent work from Kousathanas et al reported a significant genome-wide association between variants in the MUC1 gene and critical illness caused by [9,39].…”
Section: Discussionmentioning
confidence: 94%
“…Host genomic information, specifically genomic variations, may characterize susceptibility to disease and identify people with a higher risk of harm, leading to better targeting of care and vaccination [5][6][7]. In addition, characterizing these host factors may help identifying and development of adapted drugs and vaccines [8][9][10]. The scientific community came together with several efforts to investigate how the genomic variation in the host affects disease susceptibility and progress [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This protein plays a protective role against inhaled pathogens, like influenza [40]. A recent study [41] compared levels of MUC5AC, MUC1 and MUC1-CT between critical ill COVID-19 patients and healthy controls, finding a significantly higher level of those proteins in the patients' mucus. It is also worth noting that another recent work from Kousathanas et al reported a significant genome-wide association between variants in the MUC1 gene and critical illness caused by [41,42].…”
Section: Discussionmentioning
confidence: 99%